Pinch analysis and process integration a user guide on process integration for the efficient use of energy - Kemp, Ian C. (Butterworth-Heinemann, 2007)
The original guide to understanding and using pinch analysis and process integration for energy optimization.
Previous ed.: 1994, as by B. Linnhoff et al.
Keywords: Chemical plants -- Energy conservation.; Chemical processes.; Chemical process control.; elektronické knihy; electronic books